Efektivitas Canva dalam Meningkatkan Kualitas Desain Media Publikasi dan Dampaknya Terhadap Persepsi Konsumen Pariwisata di Desa Kebontunggul Mojokerto - Putri, Sasmita Aprilia; Weking, Yosefina Delong Jawa (Unri Conference Series: Community Engagement, 2024)
The development of digital technology has changed the landscape of the tourism industry. One tool that has become increasingly popular is Canva, a web-based graphic design application that offers easy visual content creation. Tourism has a close relationship with the economic sector. The existence of the tourism sector in a region can provide significant support to the region's economy. Indonesia, with its diverse natural resources that have potential as tourist destinations, has many tourist sites. Many tourist areas and villages depend on this sector to improve the local economy. An example is Kebontunggul Village, Pacet, Mojokerto Regency, which utilizes Mbencirang Valley as a tourist and outbound destination with natural beauty and attractive facilities. This study aims to test the hypothesis that the use of Canva can improve the quality of tourism publication media design and ultimately have a positive impact on consumer perceptions. Through surveys and content analysis, this research will measure changes in consumer perceptions of tourist destinations after seeing publication media designs created with Canva. The results of this study are expected to contribute to the development of a more effective tourism marketing strategy by utilizing easily accessible graphic design technology.